PENGARUH LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM - Sindy Julia; Achmad Iqbal; Adytira Rachman (JAKA - Jurnal Jurusan Akuntasi, 2023)
The purpose of this study was to analyze the effect of profitability, solvency and profitability on stock prices in manufacturing companies in the consumer goods sub-sector for the period 2019-2021. The total population of this study was 61 manufacturing companies in the consumer goods sub-sector in 2019-2021. The sampling technique used purposive sampling technique or sample research based on certain criteria with the results of 102 samples for 3 years. Data analysis using multiple linear regression. Based on the test results show that liquidity (Current Ratio) has a negative effect on Stock Price (HS). A high liquidity value (Current Ratio) is not necessarily good for the company because large funds cannot be managed properly by the company to be able to generate profits. Solvability (Debt to Equity Ratio) has no effect on stock prices (HS). This shows that increasing or decreasing Solvability (Debt to Equity Ratio) as a comparison between the company's debt and its own capital has no effect on the company's stock price. Profitability (Return on Assets) has a positive effect on stock prices. This shows that high profitability (Return on Assets) will be able to increase the company's stock price, and can attract investors' interest and can be the basis for investors' decision making to invest.